Surface bubble coalescence. (25th March 2021) - Shaw, Daniel B.; Deike, Luc
Abstract: Abstract : We present an experimental study of bubble coalescence at an air–water interface and characterize the evolution of both the underwater neck and the surface bridge. We explore a wide range of Bond number, Bo, which compares gravity and capillary forces and is a dimensionless measure of the free surface's effect on bubble geometry. The nearly spherical Bo1 bubbles exhibit the same inertial–capillary growth of the classic underwater dynamics, with limited upper surface displacement. For Bo>1, the bubbles are non-spherical – residing predominantly above the free surface – and, while an inertial–capillary scaling for the underwater neck growth is still observed, the controlling length scale is defined by the curvature of the bubbles near their contact region. With it, an inertial–capillary scaling collapses the neck contours across all Bond numbers to a universal shape. Finally, we characterize the upper surface with a simple oscillatory model which balances capillary forces and the inertia of liquid trapped at the centre of the liquid-film surface.